The impact of hedonic and utilitarian dimension in mobile service banking quality towards relationship quality - Juniarty Siahaan; Yokie Radnan Kristiyono; Anggiat B. Sitorus; Eric D. Saputra (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
Service quality is vital for retail banking institutions nowadays to have a competitive advantage against their competitors. One of the ways was developing a mobile banking application. By relying on the mobile banking application, the banking institutions would serve their existing customers better and attract new potential customers. The purpose of this research was to investigate the effect of mobile banking service quality empirically in terms of the utilitarian and hedonic dimensions on the relationship quality variables, namely commitment, trust, and satisfaction. The research focused on 220 respondents from university students in Indonesia who are at least 17 years old and using a mobile banking application on their smartphones. The method for collecting data is based on convenience sampling. The Structural Modelling Equation was also used to analyze the data result. The findings show that trust significantly and positively influences commitment/satisfaction. Furthermore, the dimensions of mobile 'banking. Service quality (Security/ Privacy, Practicality, Design/Aesthetics, and Enjoyment) has a low-moderate effect on relationship qualitative variables (Trust, Satisfaction, and Commitment). The dimensions of mobile banking service quality positively influence the relationship quality, except PPracticalitydoes not affect Commitment, Design/Aesthetics does not influence trust, and enjoyment does not influence commitment.